Effects of platelet-sparing leukocyte reduction and agitation methods on in vitro measures of hemostatic function in cold-stored whole blood. Issue 6 (June 2018) - Remy, Kenneth E.; Yazer, Mark H.; Saini, Arun; Mehanovic-Varmaz, Ajlana; Rogers, Sharon R.; Cap, Andrew P.; Spinella, Philip C.
Abstract : BACKGROUND: Agitation of platelet units stored at room temperature is performed routinely to maintain platelet function, and leukoreduction of blood products is the standard of care in many countries to reduce immune consequences of transfusion. The effect of agitation and leukoreduction on whole blood stored at 4°C requires investigation, as reductions in hemostatic capacity of whole blood may reduce its efficacy in treating trauma-induced coagulopathy and platelet dysfunction. We hypothesize that agitation of whole blood will not affect hemostatic function and that leukoreduction will reduce hemostatic function of whole blood. METHODS: In this in vitro randomized controlled study, 21 units of leukoreduced and 20 nonleukoreduced whole blood units were each randomly assigned into four agitation groups. Hemostatic parameters were measured using viscoelastic assays (rotational thromboelastometry-Extrinsic Screening Test (ROTEM-EXTEM) and thromboelastography (TEG) platelet mapping), impedance aggregometry (agonists—adenosine phosphate, arachidonic acid, thrombin receptor activating peptide, and collagen), and a thrombin generation assay from these whole blood units before and after filtration and on 0, 5, 10, and 15 days of storage at 4°C. RESULTS: Leukoreduction compared to nonleukoreduction reduced platelet concentration on Day 0. Viscoelastic measures and thrombin generation parameters revealed significant reduction in hemostatic function between the leukoreduced units and the nonleukoreduced units at a few time points. Leukoreduced units consistently demonstrated reduced platelet aggregation compared to the nonleukoreduced units. Agitation methods did not significantly affect any of the hemostatic parameters examined. CONCLUSIONS: Leukoreduction of whole blood with a platelet-sparing filter caused a moderate but significant reduction in some measures of whole blood hemostatic function most evident early in storage. The benefits of leukoreduction should be weighed against the potential reduced hemostatic function of leukoreduced units. Agitation of whole blood is not required to maintain hemostatic function. LEVEL OF EVIDENCE: In vitro randomized controlled trial, level 1. Abstract : Supplemental digital content is available in the text.